2015
DOI: 10.1016/j.jns.2015.09.349
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of matrix metalloproteinases in varicella zoster virus-infected human brain vascular adventitial fibroblasts

Abstract: Upon reactivation, varicella zoster virus (VZV) spreads transaxonally, infects cerebral arteries and causes ischemic or hemorrhagic stroke, as well as aneurysms. The mechanism(s) of VZV-induced aneurysm formation is unknown. However, matrix metalloproteinases (MMPs), which digest extracellular structural proteins in the artery wall, play a role in cerebral and aortic artery aneurysm formation and rupture. Here, we examined the effect of VZV infection on expression of MMP-1, -2, -3, and -9 in primary human brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Accumulation of monocytes/macrophages in the vascular wall can cause atherogenesis . A recent study found that the VZV induced upregulation of matrix metalloproteinases 1, 3, and 9 in brain vascular adventitial fibroblasts, which is associated with disruption of the vessel wall integrity and aneurysm formation. Previous studies also found that matrix metalloproteinases produced by inflammatory cells in virus‐infected arteries may further potentiate pathological vascular remodeling .…”
Section: Discussionmentioning
confidence: 87%
“…Accumulation of monocytes/macrophages in the vascular wall can cause atherogenesis . A recent study found that the VZV induced upregulation of matrix metalloproteinases 1, 3, and 9 in brain vascular adventitial fibroblasts, which is associated with disruption of the vessel wall integrity and aneurysm formation. Previous studies also found that matrix metalloproteinases produced by inflammatory cells in virus‐infected arteries may further potentiate pathological vascular remodeling .…”
Section: Discussionmentioning
confidence: 87%
“…Although the mechanisms of vascular remodeling triggered by VZV are unknown, neutrophils may play a role since they produce reactive oxygen species in response to infection, which may mediate smooth muscle cell proliferation and migration (Hartney et al, 2011; Weber et al, 2004) and induce apoptosis and loss of vascular smooth muscle cells (Hsieh et al, 2001; Li et al, 2003). Neutrophils also secrete elastase and matrix metalloproteinases (MMPs; together with activated matrix metalloproteinases directly secreted by VZV infected vascular cells (Nagel et al, 2015b) – these enzymes can lead to extracellular matrix breakdown, weakening of the vessel wall and aneurysm formation (Ferry et al, 1997; Itoh and Nagase, 1995; Okada and Nakanishi, 1989). Finally, a thickened intima was associated with inflammation in vaso vasorum vessels in early VZV vasculopathy, consistent with the notion that inflammatory cells secrete soluble factors that contribute to pathological vascular wall remodeling (Frid et al, 2006; Stenmark et al, 2012).…”
Section: Pathogenesismentioning
confidence: 99%
“…Consistent with studies of pathological remodeling in coronary and pulmonary arteries, the thickened intima was associated with inflammation in the underlying adventitia, supporting the notion that inflammatory cells secrete soluble factors that contribute to vascular remodeling. A recent study also revealed that VZV-infected brain vascular adventitial fibroblasts produce elevated levels of matrix metalloproteinases that degrade extracellular matrix and may contribute to migration of cells to the lumen and thrombosis as well as to aneurysm formation and hemorrhage 18 .…”
Section: Central Nervous System Disease Caused By Vzv Reactivationmentioning
confidence: 99%